Improving The Quality Of Learning Through Lifeskill Activities At SMP Muhammadiyah Ahmad Dahlan Aekkanopan - Achmad Pane, Safira; Syahputri Gumanti, Tiara; Febiyanti, Chika (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this study is to analyze activities that can improve the quality of student learning. In this article, the method used is a qualitative description method in the form of interviews and observations of teachers and students of grade 9 SMP Muhammadiyah Ahmad Dahlan Aekkanopan. Based on the results of interviews and observations, it can be concluded that life skills activities can improve the quality of student learning, this can be seen from students who have polite, brave, creative, independent attitudes, are able to manage time and are enthusiastic in participating in all learning activities that are supported by excellent school programs.